การผลิตหอยแมลงภู่ (Perna viridis Lin.) แช่เยือกแข็งแบบลมเย็น และแบบไครโอจินิค - เลิศเกียรติ พูลผล (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objective of this research was to develop the production of frozen green-lipped mussel (Perna viridis Lin.) by air blast and cryogenic freezing. Proximate composition of raw mussel was 81.88% moisture content, 9.82% protein, 1.17% fat, 2.25% ash and very low level of heavy metal. Total viable count, faecal coliforms and Escherichia coli were 2.1x10x10x10 cfu/g, 43 MPN/g and 15.7 MPN/g respectively. Blanching with either hot water or steam for 4 minutes was the suitable condition for completely destroy faecal coliforms and separate the meat from the mantle. The cryogenic freezing with liquid nitrogen was done at -70, -80, -90 and -100 ํC. Time to decrease the core temperature of the mussel to -18 ํC was 4 min, 2 min 30 sec, 2 min and 1 min 30 sec respectively. Freezing at -80 ํC was selected for further study because of least freezing loss, drip loss and high score in sensory evaluation. Concentration (5, 6, 7%) and dipping time in sodium tripolyphosphate (STP) was studied. It was found that 7% STP and dipping time of 60 sec gave the highest % weight gain and lowest % weight loss. Combination of freezing and thawing method were studied. The results revealed that freezing and thawing method had no effect on thawing loss and cutting core but % freezing loss depended on freezing method i.e. air blast gave higher % freezing loss. The shelf life storage of air blast and cryogenic freezing products were studied. It was found that % thawing loss and TBA. value increased as storage time increased while mussels which were treated with STP and glazing had less % thawing loss and TBA value. The cryogenic products and less TBA and % thawing loss than the air blast products.